The Significance of Science literacy in Biology Learning - Rizalia, Syarif; Fahrizi, Zakky; Sukmawati, Sukmawati (IAIN Kendari, 2024)
The aim of the present study is: 1) to explore the quality of teachers’ understanding about science literacy in biology; 2) to explore inhibiting and supporting factors of the quality teachers’ understanding for science literacy in biology; and 3) to suggest solutions to enhance the understanding of science literacy for biology teachers. The present study involved biology teachers and the deputy principal for curriculum of MAN 1 South Konawe. The present study is a qualitative study involving a survey with questionnaires to measure the quality of understanding of the biology teachers in terms of biology science literacy. The data analysis involves: 1) analyzing initial interview data (collection, reduction, data display, conclusion); 2) testing data validity (through source triangulation, technique triangulation, and time triangulation). The result shows that: 1) the quality of the teachers’ understanding for the science literacy in biology is interpreted based on the following indicators including the reinforcement of competence with the percentage of 36.36% which falls to into moderate category, and the support and follow-up for the development programs for literacy capability which falls into low category, accounting for 14.29%; 2) inhibiting and supporting factors for the quality of teachers’ understanding about biology science literacy is interpreted based on a number of indicators: a) both inhibiting and supporting internal factors that facilitate the implementation of science literacy-based learning, having the same influence by 50% respectively; b) external factors supporting the implementation science literacy-based learning having moderate influence of 40%, and the inhibiting external factor categorized moderate influence with the percentage of 60%; 3) Suggestions to improve the understanding of science literacy for biology teachers based on the inhibiting factors are to organize special science literacy-based activities, to create forum meetings with science literacy materials, to procure digital libraries and virtual laboratories, as well to propose various activities budgeted and disbursed by the Ministry of Religious Affairs of South Konawe. The findings suggest that developing science literacy at MAN 1 South Konawe is essential for its teachers and school’s own important significance in carrying out the biology lessons.